Pengaruh Personal Branding Yunita Siregar di Instagram terhadap Minat Membaca Buku Followers - Johanna Clarissa Kurniadi; Heppy New Year Haloho (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
Currently many public figures are doing personal branding through Instagram to build their image. One of the public figures who build personal branding through Instagram is Yunita Siregar. This research is specifically aimed at measuring the influence of personal branding carried out by Yunita Siregar on the reading interest of her followers using stimulus-response theory (S-R theory). This research uses an explanatory quantitative approach with a surveymethod to 400 respondents with categories that have been determined based on purposive sampling through distributing questionnaires to, and secondary data. Based on the results of the analysis that has been carried out, it shows that there is an influence between Yunita Siregar's personal branding on Instagram (variable X) on followers' interest in reading books (variable Y) there is an influence of 34.9% with a moderate, positive, and significant relationship level. Thus, H1 is accepted H0 is rejected.